Assessing lead and cadmium tolerance of Chenopodium ambrosioides during micropropagation: an in-depth qualitative and quantitative analysis - Jan,Tour; Khan,Nasrullah; Wahab,Muhammad; Okla,Mohammad K.; Abdel-Maksoud,Mostafa A.; Saleh,Ibrahim A.; Abu-Harirah,Hashem A.; AlRamadneh,Tareq Nayef; AbdElgawad,Hamada (PeerJ, 2023)
The tolerance of Chenopodium ambrosioides to some heavy metals under in vitro environment was thoroughly investigated. A micropropagation protocol was developed to facilitate the mass production of plants and to identify metals-tolerant species for potential use in the restoration of polluted areas. Nodal explants exhibited callus formation when treated with N6-benzyladenin (BA) (1.5 mg/l) and a combination of BA/α-naphthalene acetic acid (NAA) at concentrations of 1.5/1.0 mg/l on the Murashige and Skoog (MS) medium. The optimal shoot formation was achieved with the callus grown on a medium enriched with 1.5/1.0 mg/l BA/NAA, resulting in an impressive number (21.89) and length (11.79 cm) of shoots. The in vitro shoots were rooted using NAA (1.0 and 1.5 mg/l) and were acclimatized in pots with 71% survival rate. After standardizing micropropagation protocol, the in vitro shoots were subjected to various doses of lead nitrate (Pb(NO3)2 and cadmium chloride (CdCl2). Pb(NO3)2 and CdCl2 in the media let to a reduction in shoot multiplication, decreasing from 18.73 in the control group to 11.31 for Pb(NO3)2 and 13.89 for CdCl2 containing medium. However, Pb(NO3)2 and CdCl2 promoted shoot length from 5.61 in the control to 9.86 on Pb(NO3)2 and 12.51 on CdCl2 containing medium. In the case of Pb(NO3)2 treated shoots, the growth tolerance index (GTI) ranged from117.64% to 194.11%, whereas for CdCl2 treated shoots, the GTI ranged from 188.23% to 264.70%. Shoots treated with high level of Pb(NO3)2induced reddish-purple shoots, while a low level of Pb(NO3)2 induced shoots displayed both green and reddish-purple colors in the same explants. In CdCl2 treated culture, the toxic effects were narrow leaf lamina, elongated petiole and a dark reddish purple coloration. These findings highlight the remarkable potential of C. ambrosioides to maintain growth and organogenesis even in the presence Pb(NO3)2 and CdCl2 on the MS medium, indicating a high degree of metal tolerance.
Keywords: Chenopodium ambrosioides; Heavy metal; In-vitro culture; Phytoremediation; Tolerance